Communicative practices of perception and memory of Russian-Ukrainian war and the graphosphere of the media channel - Pavlova, Olena; Rohozha, Mariya (Studies in East European thought, 2025)
The Russian-Ukrainian war, unparalleled in scale and the number of victims in Europe since World War II, presents a substantial opportunity for the social sciences and humanities to investigate its humanitarian aspects. While concentrating on socio-political problems, we must not overlook several critical issues, such as the transformation of communicative practices of cultural memory and perception, as well as written culture as their medium, which demands distinct examination. The focus of this article is the graphosphere of the Viber channel that was active during the 2022 military operations in the city of Mariupol. It is regarded as a recorded cultural memory and perception that is/are shaped, transmitted, and preserved through the practices of new communication forms. It also illustrates how digital writing during wartime has become an incredibly informative source for scrutinizing particular facets of everyday life under extremely acute conditions. The intensity of communication through media channels has led to the prevalence of “vernacular writing on the web” and a corresponding unidirectional perception of the digital environment. Here, forms of cultural memory are mediated through the experience of witnesses. Such a Viber channel functions as a specific digital form of the graphosphere. The paper presents a case analysis of the media channel’s graphosphere within the framework of cultural studies and cultural history. These new methodological approaches in the interdisciplinary field of modern humanities allow for an examination of the transformation of cultural practices concerning memory and perception, along with their modes of documentation.